Suppression of murine type-C RNA virogenes by type-specific oncornavirus vaccines: prospects for prevention of cancer. - Huebner, R J (1976)
Immunization of crossbred and F1 mice with combined killed and live Gross leukemia virus AKR type-C viral vaccines suppressed endogeneous N-type AKR virus up to 10,000-fold for significant periods during early life. Since several previous studies in the same and similar crossbred systems revealed direct correlations between low and high levels of type-C virus early in life with low and high incidences of leukemia and other cancers later in life, we believe that prospects for suppression of spontaneous neoplasms are good; however, 8-14 months will be required to achieve the final results. Should cancers be prevented by serotype-specific vaccines, such evidence would provide conclusive proof of endogenous viral etiology.